Semiotic design for warning signs to allergic reactions arising from the use of hair care products / Muhamad Irsaffuddin Ismail and Azhar Abd Jamil - Ismail, Muhamad Irsaffuddin; Abd Jamil, Azhar (Universiti Teknologi MARA, 2018)
Hair care products are generally utilised for medical purposes such as personal hygiene, skin improvement, anti-aging conditions and self-confidence. Nevertheless, some of the hair care products containing prohibited substances could cause adverse effect to the consumers. Normally, consumers are unaware of the substances used in hair care products due to lack of information and awareness. Currently the design on hair care products does not indicate any warning signs or warning symbols that informs of side effects or allergies. Semiotic designs evaluate the process by which signs and symbols come to have meaning. The concern on how signs are developed and interpreted based on scientific symptoms is the main focus of this research. The study on various scientific symptoms reactions caused by the hair care products were then translated to visual signs. Semiotic designs are one of the important components in designing symbols and icons, thus helping consumers understand the meaning of each symptoms through visual signs. A series of pictograms were created based on the six categories of allergic reactions. Feedbacks from the sampling/users were utilised to identify the effectiveness of warning signs.